Question
upstudy study bank question image url

The function \( f \) is given by \( f(x)=4 \cdot 3^{(z-2)}+1 \). The function \( g \) is given by \( g(x)=f^{-1}(x) \). For which of the following values does \( g(x)=-3 x \) ?

Ask by Rodriquez Lyons. in the United States
Jan 30,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

To find the values of \( x \) where \( g(x) = -3x \), first find the inverse function \( g(x) = f^{-1}(x) \) of \( f(x) = 4 \cdot 3^{(x-2)} + 1 \). Setting \( g(x) = -3x \) leads to a complex equation that may require numerical methods to solve. After testing integer values, no exact solutions are found within the tested range.

Solution

To find the values for which \( g(x) = -3x \), we first need to determine the inverse function \( g(x) = f^{-1}(x) \) of the function \( f(x) = 4 \cdot 3^{(x-2)} + 1 \). ### Step 1: Find the inverse function \( f^{-1}(x) \) 1. Start with the equation for \( f(x) \): \[ y = 4 \cdot 3^{(x-2)} + 1 \] 2. Rearrange the equation to solve for \( x \): \[ y - 1 = 4 \cdot 3^{(x-2)} \] \[ \frac{y - 1}{4} = 3^{(x-2)} \] 3. Take the logarithm of both sides: \[ \log_3\left(\frac{y - 1}{4}\right) = x - 2 \] 4. Solve for \( x \): \[ x = \log_3\left(\frac{y - 1}{4}\right) + 2 \] Thus, the inverse function is: \[ f^{-1}(x) = \log_3\left(\frac{x - 1}{4}\right) + 2 \] ### Step 2: Set up the equation \( g(x) = -3x \) Now we set \( g(x) = f^{-1}(x) \) equal to \( -3x \): \[ \log_3\left(\frac{x - 1}{4}\right) + 2 = -3x \] ### Step 3: Solve the equation 1. Rearranging gives: \[ \log_3\left(\frac{x - 1}{4}\right) = -3x - 2 \] 2. Exponentiating both sides to eliminate the logarithm: \[ \frac{x - 1}{4} = 3^{-3x - 2} \] 3. Multiply both sides by 4: \[ x - 1 = 4 \cdot 3^{-3x - 2} \] \[ x - 1 = \frac{4}{9} \cdot 3^{-3x} \] 4. Rearranging gives: \[ x - 1 = \frac{4}{9} \cdot \frac{1}{3^{3x}} \] ### Step 4: Solve for \( x \) This equation is complex and may require numerical methods or graphing to find solutions. However, we can also check specific values of \( x \) to see if they satisfy the equation. Let's check some integer values for \( x \): - For \( x = 0 \): \[ 0 - 1 = -1 \quad \text{and} \quad \frac{4}{9} \cdot 3^{0} = \frac{4}{9} \quad \text{(not equal)} \] - For \( x = 1 \): \[ 1 - 1 = 0 \quad \text{and} \quad \frac{4}{9} \cdot 3^{-3} = \frac{4}{9} \cdot \frac{1}{27} = \frac{4}{243} \quad \text{(not equal)} \] - For \( x = -1 \): \[ -1 - 1 = -2 \quad \text{and} \quad \frac{4}{9} \cdot 3^{3} = \frac{4}{9} \cdot 27 = 12 \quad \text{(not equal)} \] - For \( x = -2 \): \[ -2 - 1 = -3 \quad \text{and} \quad \frac{4}{9} \cdot 3^{6} = \frac{4}{9} \cdot 729 = 324 \quad \text{(not equal)} \] Continuing this process or using numerical methods will yield the specific values of \( x \) for which \( g(x) = -3x \). ### Conclusion To find the exact values, numerical methods or graphing tools may be necessary. Would you like me to perform a numerical solution for this equation?

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve for the values of \( x \) where \( g(x) = -3x \) given the function \( f(x) = 4 \cdot 3^{(x-2)} + 1 \), we first need to find the inverse function \( g(x) = f^{-1}(x) \). 1. Set \( y = f(x) \): \[ y = 4 \cdot 3^{(x-2)} + 1 \] Rearranging gives: \[ y - 1 = 4 \cdot 3^{(x-2)} \] Dividing both sides by 4: \[ \frac{y - 1}{4} = 3^{(x-2)} \] Taking the logarithm base 3 on both sides: \[ x - 2 = \log_3\left(\frac{y - 1}{4}\right) \] Thus, we obtain: \[ x = 2 + \log_3\left(\frac{y - 1}{4}\right) \] So, the inverse function is: \[ g(y) = 2 + \log_3\left(\frac{y - 1}{4}\right) \] 2. Next, we need to set this equal to \( -3x \): \[ 2 + \log_3\left(\frac{x - 1}{4}\right) = -3x \] 3. Solve for \( x \): \[ \log_3\left(\frac{x - 1}{4}\right) = -3x - 2 \] Exponentiating both sides with base 3 gives: \[ \frac{x - 1}{4} = 3^{-3x - 2} \] Therefore, \[ x - 1 = 4 \cdot 3^{-3x - 2} \] \[ x = 4 \cdot 3^{-3x - 2} + 1 \] While the equation is complex to solve algebraically, we can approach values to find solutions numerically or graphically. 4. By testing values: - For \( x = 0 \): \[ g(0) = f^{-1}(0) \text{ does not exist since } f(x) = 1 \text{ for all } x. \] - For \( x = -1 \): \[ -3(-1) = 3; \text{ check if } g(3) = 3. \] - Continue testing further values until you find points of intersection. This leads to finding specific values where the condition holds. Therefore, \( g(x) = -3x \) can be solved for values in the set \( x \) based on calculations or rooting towards equations generated via numerical estimation. Upon deeper exploration, typically using graphing or numerical tools (e.g., plotting both functions or utilizing numerical solvers), we can identify specific intersections leading to properties of the inverse function at respective coordinates. Thus, the solution set can be found through exploration within the bounds of possible values or estimated numerical values.

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy